2013
DOI: 10.1111/jphp.12117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasticiser type on the hot melt extrusion of venlafaxine hydrochloride

Abstract: CAMH and Lutrol have different reactivities towards venlafaxine HCl and also different plasticising mechanisms for Eudragit RSPO because of hydrogen bonding and because of similar overall molecular attractive forces, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[111] in 26.1% of the CAMS prepared by the thermodynamic pathway and 20.4% were obtained by solvent removal, which is a method commonly used to obtain (co-)crystals but also exploited for the formulation of CAMS [92]. Other preparation methods include for example inkjet-printing (thermodynamic pathway) [93], hot melt extrusion (mainly thermodynamic pathway) [94][95][96], in situ co-amorphization [97][98][99][100], co-precipitation (thermodynamic pathway) [101], and co-grinding (kinetic pathway; defined as manually grinded) [102], of which some are difficult to assign to a certain pathway (thermodynamic or kinetic). Interestingly, in some cases, depending on the used preparation method, a drug and a co-former could form a CAMS or not.…”
Section: Preparation Methods Of Camsmentioning
confidence: 99%
See 1 more Smart Citation
“…[111] in 26.1% of the CAMS prepared by the thermodynamic pathway and 20.4% were obtained by solvent removal, which is a method commonly used to obtain (co-)crystals but also exploited for the formulation of CAMS [92]. Other preparation methods include for example inkjet-printing (thermodynamic pathway) [93], hot melt extrusion (mainly thermodynamic pathway) [94][95][96], in situ co-amorphization [97][98][99][100], co-precipitation (thermodynamic pathway) [101], and co-grinding (kinetic pathway; defined as manually grinded) [102], of which some are difficult to assign to a certain pathway (thermodynamic or kinetic). Interestingly, in some cases, depending on the used preparation method, a drug and a co-former could form a CAMS or not.…”
Section: Preparation Methods Of Camsmentioning
confidence: 99%
“…Despite these promising examples using ternary CAMS, potential risks should also be taken into consideration. A similar concept (i.e., adding a small molecule into ASDs to improve the performance of ASDs) has been applied in the polymer ASD research [96,152]. However, it was recently discovered that the addition of saccharin or tryptophan resulted in a decreased physical stability of carbamazepine-PVP ASD in both predictions and experiment validations [56].…”
Section: Acyclovirmentioning
confidence: 99%
“…Materials with similar δ t values are considered miscible or that one can dissolve in the other. Therefore, comparison of δ t values can be used to predict miscibility of PG with the examined polymers [30]. From the values given in Table 2, it can be seen that the contribution of dispersive forces (δ d ) is similar for all materials, but the polar (δ p ) and H-bonding (δ hb ) components are different, with cellulose-based excipients showing higher δ p , δ hb and hence, higher δ t values (from 30.6 to 39.3 MPa 1/2 compared with 18.9 to 21.9 MPa 1/2 ).…”
Section: Hansen Solubility Parametersmentioning
confidence: 99%
“…Small differences in the molecular arrangement and/or environment due to non-specific intermolecular interactions, H-bonds or π−π interactions underline interactions and formation of heterodimers [ 12 , 66 ]. Changes in the FTIR spectra may also indicate salt formation e.g., between IND and ARG in co-amorphous SDs or even esterification e.g., between venlafaxine and citric acid [ 55 , 67 ].…”
Section: Solid State Characterizationmentioning
confidence: 99%
“…PEO reduced the melt viscosity, prevented phase separation (despite Tg reduction) and resulted in a ternary amorphous SD where PEO acted as co-solvent for both drugs. Bounartzi et al [ 67 ] applied HME using the ternary mixture citric acid-Eudragit RSPO-venlafaxine hydrochloride (CA-RSPO-VEN) and produced co-amorphous transparent SD. Since in the binary CA-VEN extrudate some crystalline reflections of plasticizer existed, it was concluded that the matrix polymer was essential for the formation and stabilization of the CA-VEN co-amorphous dispersion.…”
Section: Preparation Of Co-amorphous Solid Dispersionsmentioning
confidence: 99%